2014
DOI: 10.1523/jneurosci.0391-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Differential Longitudinal Changes in Cortical Thickness, Surface Area and Volume across the Adult Life Span: Regions of Accelerating and Decelerating Change

Abstract: Human cortical thickness and surface area are genetically independent, emerge through different neurobiological events during development, and are sensitive to different clinical conditions. However, the relationship between changes in the two over time is unknown. Additionally, longitudinal studies have almost invariably been restricted to older adults, precluding the delineation of adult life span trajectories of change in cortical structure. In this longitudinal study, we investigated changes in cortical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
458
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(531 citation statements)
references
References 59 publications
(7 reference statements)
57
458
3
2
Order By: Relevance
“…As indicated by our analysis, CSA and CT can be partly conceived as being distinct traits, and thus their analysis provides more nuanced information than the sole computation of CV as implemented in VBM. Given this understanding, the present study concurs with a pool of recent reports which also demonstrated the genetically and phenotypically distinctiveness of CT and CSA [38,39,41,40,42,43,65,44,45,46]. It is important to mention that CV cannot be interpreted as a simple compilation of CT and CSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As indicated by our analysis, CSA and CT can be partly conceived as being distinct traits, and thus their analysis provides more nuanced information than the sole computation of CV as implemented in VBM. Given this understanding, the present study concurs with a pool of recent reports which also demonstrated the genetically and phenotypically distinctiveness of CT and CSA [38,39,41,40,42,43,65,44,45,46]. It is important to mention that CV cannot be interpreted as a simple compilation of CT and CSA.…”
Section: Discussionsupporting
confidence: 91%
“…The substantial discrepancy between studies is confusing and makes the interpretation of the (sometimes conflicting) data problematic. The methodological impediments that may complicate the comparability of studies on structural neuroplasticity in tinnitus are small sample sizes, comorbid psychological problems, differences in TI's 65 age of onset and duration, that is the interval between tinnitus onset and the time point of data acquisition. Furthermore, evidence for confined "structural abnormalities specifically related to tinnitus is sparse" [33, p. 119], and this fact makes it difficult to test specific anatomical hypotheses.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…We suggest that these effects may in some cases be overestimated, particularly in certain brain locations, by the inclusion of biased estimates from T1w structural scans with motion artifacts. The present work leveraged the variability in head motion and morphometry in a healthy adult sample to show that: (1) independent estimates of motion significantly predicted GM thickness (independent of age and gender), and (2) motion slightly but significantly biased thickness estimates in several regions that are often highlighted to undergo cortical thinning with increasing age [e.g., medial PFC, cingulate cortex, precuneus, IFG and anterior insula, SMG, lateral temporal cortex; Fjell et al, 2009; Lemaitre et al, 2012; Raz et al, 2005; Salat et al, 2004; Storsve et al, 2014]. …”
Section: Discussionmentioning
confidence: 99%
“…Cortical thickness and area are determined by different processes in embryonic cortical development 26 and appear influenced by unrelated genetic mechanisms. 27 Furthermore, thickness and area show different trajectories in the normal aging brain, 28 and may be affected differently by disease processes. It is therefore of interest to investigate these 2 components independently.…”
Section: Introductionmentioning
confidence: 99%